2004
DOI: 10.3168/jds.s0022-0302(04)73378-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biotin Supplementation on Peripartum Performance and Metabolites of Holstein Cows

Abstract: Fifty-two multiparous Holstein cows were randomly assigned to receive 0 or 20 mg of biotin/d starting at an average of 16 d prepartum and then switched to 0 or 30 mg of biotin/d from calving through 70 d postpartum to determine whether supplemental biotin would affect cow performance, hepatic lipidosis, and plasma metabolites. Mean concentration of biotin in plasma sampled weekly was greater in cows fed biotin (4.3 vs. 9.4 nmol/L). Postpartum dry matter intake as a percentage of body weight (3.9% vs. 4.0%), mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
7
14

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 28 publications
4
24
7
14
Order By: Relevance
“…Reasons for the increase in jugular vein plasma glucose concentration reported by Bonomi et al (1996) and Rosendo et al (2004) are not certain. An increased supply of oxaloacetate via a stimulation of carboxylase activity in the liver would only be used for glucose synthesis if the additional oxaloacetate was required (Reynolds, 1995).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Reasons for the increase in jugular vein plasma glucose concentration reported by Bonomi et al (1996) and Rosendo et al (2004) are not certain. An increased supply of oxaloacetate via a stimulation of carboxylase activity in the liver would only be used for glucose synthesis if the additional oxaloacetate was required (Reynolds, 1995).…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, DM offered was restricted to just below ad libitum and not altered over the course of the study to reduce variation in nutrient absorption and metabolism by splanchnic tissues attributable to DMI. In dairy cows fed ad libitum, supplemental biotin has typically increased milk yield (Bonomi et al, 1996;Midla et al, 1998;Zimmerly and Weiss, 2001;Bergsten et al, 2003;Majee et al, 2003) but the effect has not been observed in every study reported (Fitzgerald et al, 2000;Rosendo et al, 2004). In the present study, the lack of a milk yield response to supplemental biotin may have been due to the restricted DMI of the cows, or the length of supplementation (14 days) may have been too short to allow for effects on milk yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other studies have shown that dairy cows could in fact benefit from biotin supplementation, most of those studies used a daily dietary supplementation of 20 mg of biotin. Table 1 shows the effects of biotin supplementation on the production performance of dairy cows in studies specifically designed for that purpose (Bonomi et al 1996;Zimmerly and Weiss 2001;Majee et al 2003;Rosendo et al 2004) and in studies focusing on foot lesions (Cooke and Brumby 1982;Midla et al 1998;Fitzgerald et al 2000;Bergsten et al 2003). In summary, supplementary biotin was found to increase milk yield in five out of eight studies.…”
Section: Vitamin B 12mentioning
confidence: 99%
“…Ferreira et al (2007) stressed that supplementary biotin was more likely to increase milk and milk component yields in highproducing cows than in low-producing ones because the metabolic demand was greater in the former. Nevertheless, in some studies, high-producing cows did not respond to biotin supplementation (Rosendo et al, 2004). In 2011, two meta-analyses on the effects of dietary supplements of biotin on milk production and composition of Holstein dairy cows were published (Chen et al, 2011;Lean and Rabiee, 2011).…”
Section: Biotinmentioning
confidence: 99%